Risk and Real Estate Investment in Ghana - Imran, S. T. (University of Ghana, 2015)
Residential real estate, in recent times, has attracted a lot of attention due to its strong economic performance which is mainly as a result of increasing demand for housing and additional diversification benefits offered to investors in the region; making real estate investment extremely lucrative. Nonetheless many investors have doubts about the prudence of investing in emerging markets. In particular it may be felt that the expected returns offered in the countries of the African region are not sufficient to compensate investors for the increased risks of investing in such markets. These risks can be categorized under four headings: credit risk, market risk, operational risk, and liquidity risk. So in determining the extent to which systematic risks (those looked at in this work were GDP growth rate, Interest rate, Exchange rate, Inflation rate, Unemployment rate and Number of houses sold) influence investment returns in the Ghanaian housing market, this paper adopted a Vector Autoregressive Model where each of these risks were examined in turn to see if they were sufficiently large to deter real estate investment in the region in general. From this the study it was found that shocks to the expected returns, the GDP growth rate, and the interest rate explained about 90% of the movement of the expected returns, indicating that these variables are good at transmitting the effects of shocks to the housing market. This showed that investors would have to look at these areas as target areas when adopting risk management measures in order to maximize their returns.
Thesis (MPhil.) - University of Ghana, 2015